Analisis Teori Fungsionalisme pada Integrasi Kawasan Asia Selatan (Studi Kasus Konflik India-Pakistan di wilayah Kashmir) - Tri Shinta (Jurnal Sentris, 2019)
South Asia is a complex region. It is marked with the emergence and continuity of the conflict. India-Pakistan conflict is one of them. This conflict begun on 1947 and the biggest of conflict divided into three conflicts. Functionalism according to David Mitrany in “A Working Peace System” believes that Region Integration is trusted to make the conflict lower and good relation among state. This perception applied on 1985 in South Asia, which known with SAARC (The South Asian Association for Regional Cooperation). The fact, this conflict still continues till today. However, this paper seeks for the analysis of how’s functionalism theory explain the conflict of India-Pakistan on the regional integration: is that the conflict form an ideal integration of Sout Asia and decline the conflict, or conversely. Furthermore, the result of this research describes that Functionalism is not success on explaining South Asia integration, which means the India-Pakistan conflict still exist and the real integration among member states still not exist yet.